2013
DOI: 10.1371/journal.pone.0062002
|View full text |Cite
|
Sign up to set email alerts
|

CD271 Defines a Stem Cell-Like Population in Hypopharyngeal Cancer

Abstract: Cancer stem cells contribute to the malignant phenotypes of a variety of cancers, but markers to identify human hypopharyngeal cancer (HPC) stem cells remain poorly understood. Here, we report that the CD271+ population sorted from xenotransplanted HPCs possesses an enhanced tumor-initiating capability in immunodeficient mice. Tumors generated from the CD271+ cells contained both CD271+ and CD271− cells, indicating that the population could undergo differentiation. Immunohistological analyses of the tumors rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 46 publications
7
70
0
Order By: Relevance
“…S5). The CCL19 þ CD271 þ tumor cells may be cancer stem cells (CSC) because CD271 is one of the representative markers for CSCs in some cancers (24,25). tative RT-PCR, both ccl19 and cd271 mRNA expressions increased significantly and correlatively with herv-h mRNA expression (P < 0.01; Fig.…”
Section: A Close Connection Between Herv-h/ccl19 Expression In Tumor mentioning
confidence: 95%
“…S5). The CCL19 þ CD271 þ tumor cells may be cancer stem cells (CSC) because CD271 is one of the representative markers for CSCs in some cancers (24,25). tative RT-PCR, both ccl19 and cd271 mRNA expressions increased significantly and correlatively with herv-h mRNA expression (P < 0.01; Fig.…”
Section: A Close Connection Between Herv-h/ccl19 Expression In Tumor mentioning
confidence: 95%
“…(14) We also reported that CD271 is a marker of CSC in hypopharyngeal cancer and that high levels of CD271 expression in tumor tissues correlate with a poor prognosis. (15) However, little is known about the surface marker of CSC in cholangiocarcinoma. Since CSC initiate the tumor-forming process, they are expected to provide optimal target(s) for therapy.…”
mentioning
confidence: 99%
“…NGFR has been identified as a marker of cells with these properties in multiple malignancies, including head and neck squamous cell carcinoma [4, 32]. Here, we report the identification of a novel downstream target gene of NGFR, ESM1 .…”
Section: Discussionmentioning
confidence: 80%